The Antibactrial and Antifungal Activity of Salix Aegypitica L Root and Leave Extraction - SOFI, SHNO ABDALQADIR; ABDALRAHMAN, MAAROOF RASUL (The journal of contemporary issues in business and government, 2021)
Musk Willow is also known as Salix aegyptiaca L. In the Middle East, especially in Iran, S. aegyptiaca extracts and essential oils are important areas in drug production with some pharmacological activities. S. aegyptiaca has long been used in herbal medicine to treat anemia and vertigo, as well as a cardiotonic and a fragrance additive in the preparation of local candies. Recently, it was discovered that S. aegyptiaca has antioxidant, anxiolytic, and hypocholesterolemic properties. The leaves of this plant contain high levels of phenols and flavonoids such as gallic acid, caffeic acid, myricetin, catechin, quercetin, and salicin. The major constituents of the essential oil in leaves of S. aegyptiaca were classified as 1,4- dimethoxybenzene, phenylethyl alcohol, carvone, citronellol, methyleugenol, eugenol, n- tetradecane, and 4-methoxyacetophenone. This plant has become both food and medicine in Iran due to its ease of selection, widespread distribution, and remarkable biological activities. This review provides in-depth analysis of the botanical, chemical, and pharmacological aspects of Aedes aegyptiaca.